2012
DOI: 10.1080/03115518.2012.645632
|View full text |Cite
|
Sign up to set email alerts
|

The generaCryptaulaxandProcerithium(Procerithiidae, Caenogastropoda) in the Early Jurassic of Patagonia, Argentina

Abstract: New species of Cryptaulax and Procerithium (Procerithiidae, Caenogastropoda) are reported from the Lower Jurassic (Pliensbachian-Toarcian) marine deposits of west-central Chubut province, Argentinean Patagonia. Three new species are described: Cryptaulax redelii, Procerithium (Rhabdocolpus) patagoniensis and Procerithium (Infacerithum) nodosum; and the diagnoses of Cryptaulax damboreneae Ferrari and Procerithium nulloi (Ferrari) are emended. The new fossils derive from the Mulanguin˜eu and Osta Arena formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…(Fig. 3O) are frequently found in the Jurassic marine sandstones of the Chubut Province in shallow environments, associated to diverse invertebrate faunas, but rarely mixed with Lithotrochus (Ferrari, 2012(Ferrari, , 2014a.…”
Section: Gastropodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Fig. 3O) are frequently found in the Jurassic marine sandstones of the Chubut Province in shallow environments, associated to diverse invertebrate faunas, but rarely mixed with Lithotrochus (Ferrari, 2012(Ferrari, , 2014a.…”
Section: Gastropodsmentioning
confidence: 99%
“…Bivalves, gastropods, cephalopods, brachiopods and corals were reported by these authors from several localities in the area, including Lomas Occidentales, Cerro La Trampa, Piedra Shotle and Lomas de Betancourt, which have yielded the most important Jurassic fossiliferous beds from the marine Mulanguiñeu Formation (Chubut Province). Another important marine locality was reported at the Early Jurassic of the Osta Arena Formation from the Pampa de Agnia region (central Chubut Province), known as Puesto Currumil (Ferrari, 2009(Ferrari, , 2012(Ferrari, , 2013Pagani et al, 2012). Preliminary biostratigraphic analyses carried out in the southern and west-central Chubut Province (Pagani et al, 2012;Ferrari, 2013Ferrari, , 2014a indicated a late Pliensbachian-early Toarcian age for these deposits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several Argentinean Early Jurassic marine gastropods have been described by Ferrari (2009Ferrari ( , 2011Ferrari ( , 2012Ferrari ( , 2013Ferrari ( , 2014aFerrari ( , 2014b and Ferrari et al (2014) from the Chubut Province. Up to date, 13 gastropod families from the Early Jurassic (late Pliensbachianearly Toarcian) marine deposits of the Mulanguiñeu and Osta Arena formations (Chubut Province), representing 20 genera, 2 subgenera and at least 30 species are reported.…”
Section: Introductionmentioning
confidence: 99%
“…Damborenea et al (1975) preliminarily reported 15 gastropod species from the late Pliensbachian beds at Piedra Pintada (southern Neuquén), and Ferrari et al (in press) contributed to the paleontological knowledge of the family Trochotomidae in the Early Jurassic of the Neuquén basin. Recently, Ferrari (2011Ferrari ( , 2012Ferrari ( , 2013Ferrari ( , 2014aFerrari ( , 2014b Ferrari et al (2014) has described in detail and referred many gastropod species from Argentina to the genera Chartronella, Calliotropis, Ambercyclus, Colpomphalus, Cryptaenia, Guidonia, Hamusina, Jurassiphorus, Procerithium, Cryptaulax, Oonia, Striactaeonina, Actaeonina. Most of the species described thus far from Argentina show close taxonomic affinities to the Late Triassic gastropod faunas reported by Haas (1953) from the Pucará Group of Central Perú.…”
Section: Introductionmentioning
confidence: 99%